2023
DOI: 10.1111/andr.13439
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene intake and the risk of erectile dysfunction in US adults: NHANES 2001–2004

Abstract: BackgroundErectile dysfunction is a condition with a high incidence among adult men. Lycopene has been shown to lower blood glucose and reduce weight in diabetic patients because of its antioxidant and anti‐inflammatory properties. However, the association between lycopene and the incidence of erectile dysfunction is unclear.ObjectiveThe aim of this study was to examine the dietary lycopene intake and its association with erectile dysfunction risk in the US population.Materials and methodsWe investigated the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The main limitation of this study is the use of a self-reported questionnaire method to assess ED, which may not accurately reflect the true prevalence of ED. However, the validity of the measurement in our study has been previously tested, and the prevalence of ED in our study was similar to previous reports, which increases our confidence in the results ( 22 , 34 , 35 ). We posit that self-reported experiences of ED may be more relevant for perceived social support than objectively assessed ED.…”
Section: Discussionsupporting
confidence: 91%
“…The main limitation of this study is the use of a self-reported questionnaire method to assess ED, which may not accurately reflect the true prevalence of ED. However, the validity of the measurement in our study has been previously tested, and the prevalence of ED in our study was similar to previous reports, which increases our confidence in the results ( 22 , 34 , 35 ). We posit that self-reported experiences of ED may be more relevant for perceived social support than objectively assessed ED.…”
Section: Discussionsupporting
confidence: 91%
“… 42–44 HDL-C also downregulates neutrophil/monocyte infiltration of the arterial wall media/intima. 45 In addition, the effects of inflammatory activation of LDL-C endothelial cells are inhibited by HDL-C, mainly by reducing the oxidation of LDL-C. 45 HDL-C also increases the expression of endothelial nitric oxide synthase, which acts as a vasodilator. 46 …”
Section: Discussionmentioning
confidence: 99%